Survey of Midbrain, Diencephalon, and Hypothalamus Neuroanatomic Terms Whose Prosomeric Definition Conflicts With Columnar Tradition - Puelles, Luis (Frontiers in Neuroanatomy, 2019)
Recent neuroanatomic concepts and terms referring to the non-telencephalic forebrain are presented and discussed, in context with the present scenario in which the old columnar paradigm is being substituted by the prosomeric model, largely on the basis of novel molecular and experimental evidence.